Bolivia at a Crossroads: Is Consolidation of a ‘Divided Society’ Feasible? - T. A. Vorotnikova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
A protest wave which began in 2019 has swept across many Latin American countries. The Multinational State of Bolivia, where rapid destabilization of political situation has led to a serious internal crisis, was no exception. The paper examines the prospects for conﬂict resolution in Bolivia through the lens of the ‘divided society’ concept. The ﬁrst section identiﬁes the key fault lines in Bolivia including ethnic, cultural, and civilizational diﬀerences, economic disproportions, and high levels of social and political polarization. The author shows how the regime of Evo Morales managed to reach an internal balance and maintain it for quite a long time through complex balancing, concessions, and compromises. The second section identiﬁes the causes behind the 2019 crisis. These include miscalculations of the government which has revealed general instability of the country’s political system and threatened to erode democratic institutions; changes in electoral behavior of the population; the increasing role of the armed forces. The author links the possibilities to overcome these challenges faced by Bolivia with the expansion of the social protection in conjunction with the principle of consociationalism, but stresses that even so the consolidation of the Bolivian society will be a time-consuming process.